Factors influencing the development of attitudes towards men who sexually offend and the impact on their care and treatment: A systematic review of literature between 1985 and 2015. (July 2018) - Challinor, Laura; Duff, Simon
Abstract: Background: Research has investigated the attitudes of a range of professional and paraprofessional staff who are exposed to men who have sexually offended. The evidence emerging from this work suggests that many factors appear to have an effect on the attitudes that staff develop, including the number of years in their job, gender, or parental status. Objectives: The aim of this review is to explore these factors to determine the influence they have on the attitudes of care staff and how these attitudes subsequently influence the care and treatment provided to men who sexually offend. Method: An electronic search of seven bibliographic databases was conducted to identify primary research studies in addition to scanning reference lists of existing studies and contacting experts in the field. The search generated 13, 987 hits. After scanning the titles and abstracts, 51 papers were subject to the exclusion criteria. A total of 13 studies met the inclusion criteria and were included in the final synthesis process. Results: A number of factors appear to be important when exploring the relationship between attitudes and the care and treatment provided to men who sexually offend. These include factors within the domains of cognitive, affective and behavioural attitudes. Conclusions: The papers highlighted a range of factors that influence attitudes. These factors appear to influence the flavour of attitudes and the nature of attitudes is seen to be an influencing factor in terms of the quality of relationships between men who commit sexual offences and professional staff. However the definition of attitudes needs to be more carefully applied to empirical research. Results collected from the studies provide suggestions regarding the clinical implications. Highlights: The factors that were found to be important fall within three domains; cognitive, affective and behavioural. Cognitive factors included occupational exposure to men who sexually offend. Affective factors included empathy. Behavioural factors included job role.